Effects of the tropical climate on the reference ranges of serum biochemistry in athletic horses - Padilha, F. G. F.; Meriade, G. B.; Ferreira, A. M. R. (Journal of Equine Veterinary Science, 2021)
The purpose of this study was to establish the reference ranges of serum biochemistry parameters of Brazilian Sport Horses undergoing training in a tropical climate. Eighty-nine Brazilian Sport Horses (4 to 11 years; castrated males and females) that were training and competing for equestrian disciplines (showjumping, dressage and eventing) in a tropical climate were selected for this study. All horses had, at least, 48 h of rest before the vacuum venipuncture of the external jugular vein. Approximately, 8mL of venous blood were collected in tubes without anticoagulant to perform the serum biochemical analysis. The parameters analyzed were aspartate transaminase (AST), creatine kinase (CK), urea, creatinine, alanine transaminase (ALT), gamma-glutamyl transferase (GGT), albumin and calcium by an automatic spectrophotometer. The reported values were applied to the probability density function formula and were described as a normal distribution. The Tukey Test was used to determine the minimum and maximum limits using the 5 and 95% percentiles. Most of the parameters were within the reference interval indicated, except for CK and albumin, in which 93.25% and 94.38% of the horses, respectively, presented the results considered normal (Table 1). This alteration can be explained by muscular lesion due to excessive training and to dehydration in reason of the high temperatures and humidity. This information was confirmed by clinical examination. The study was done by the end of the equestrian season, which may explain these results. It is known that the training protocol the horses are imposed to may lead to overtraining. The loss of performance and the observance of different clinical signs such as reluctance to move, lameness and increased skin-pinch test may be important to help the diagnosis. In conclusion, the tropical climate influenced the results of athletic horses, altering CK and albumin. It is important to analyze data respecting the geographical location, climate, breed, and type of exercise. It suggests the reference range method as a technique to evaluate some parameters of a specific sample and which can be applied to animals of similar characteristics.